Influence of experimental parameters on the side reactions of hydrosilylation of allyl polyethers studied by a fractional factorial design. Issue 5 (25th July 2018) - Bouvet-Marchand, A.; Chatard, C.; Graillot, A.; Boutevin, G.; Loubat, C.; Grosso, D.
Abstract : Comprehensive study of the hydrosilylation of allyl polyethers using the methodology of a design of experiments. Abstract : Even though the hydrosilylation reaction has been the method of choice to produce organosilicon compounds for 70 years, improving its selectivity still remains a current challenge. In this work, a comprehensive study of the influence of experimental parameters on hydrosilylation side reactions was undertaken by applying a fractional factorial design of experiments. The study was conducted for polyethylene glycol (PEG, 1000 g mol −1 ) terminated allyl ether, which is commonly employed as a reactive functional group toward hydrosilylation. In addition, the resulting silane-functionalized PEG happens to be a molecule of interest in various domains such as the biomedical, cosmetic or food industry thanks to its properties in accordance with these sectors' requirements. This methodology enables highlighting an optimized combination of experimental parameters as well as a cause–effect relationship between the different side reactions, leading to a better control of the hydrosilylation reaction.